Agroforestry and Sustainable Agricultural Production - Rolo, Victor (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the potential of agroforestry to maximize agriculture production while minimizing negative effects on the environment. It collects several studies on agroforestry systems from around the world, including a variety of types of agroforestry systems, from traditional wood-pastures to tropical cocoa-based systems, and research approaches, from literature reviews to state-of-the-art ecological-economic models. The book highlights the potential of agroforestry as a promising approach for the creation of multifunctional landscapes able to face contemporary environmental challenges.